A Place for Everything with Everything in its Place! - Dow Chemical Company (1950)
Color print advertisement for Styron, the trade name for Styrenic plastics historically manufactured and sold by the Dow Chemical Company for a variety of consumer applications. The advertisement features an illustration of a woman in an apron posing in front of an open refrigerator, framed by illustrations of refrigerator parts made from Styron. The accompanying text describes the qualities of Styron that make it suitable for plastic parts in refrigerators. This advertisement appeared in a 1950 edition of Ladies' Home Journal.
Keywords: Advertising; Dow Chemical Company; Chemical industry; Corporations; Plastics; Plastics industry and trade; Women in advertising; Housewives; Housewives as consumers; Household appliances; Advertising, Industrial; Consumer goods